Nyamiviridae: Proposal for a new family in the order Mononegavirales - Kuhn, Jens H.; Bekal, Sadia; Caì, Yíngyún; Clawson, Anna N.; Domier, Leslie L.; Herrel, Marieke; Jahrling, Peter B.; Kondo, Hideki; Lambert, Kris N.; Mihindukulasuriya, Kathie A.; Nowotny, Norbert; Radoshitzky, Sheli R.; et al. (Archives of virology, 2013)
Nyamanini virus (NYMV) and Midway virus (MIDWV) are unclassified tick-borne agents that infect land birds and seabirds, respectively. The recent molecular characterization of both viruses confirmed their already known close serological relationship and revealed them to be nonsegmented, single- and negative-stranded RNA viruses that are clearly related to, but quite distinct from, members of the order Mononegavirales (bornaviruses, filoviruses, paramyxoviruses, and rhabdoviruses). A third agent, soybean cyst nematode virus 1 (SbCNV-1, previously named soybean cyst nematode nyavirus), was recently found to be an additional member of this new virus group. Here, we review the current knowledge about all three viruses and propose classifying them as members of a new mononegaviral family, Nyamiviridae .